Liming agricultural soils in Western Kenya: Can long-term economic and environmental benefits pay off short term investments? - Hijbeek, Renske; Loon, Marloes P. van; Ouaret, Walid; Boekelo, Batiaen; Ittersum, Martin van (Elsevier, 2021)
Context Soil acidification affects crop yields which can diminish farmers' incomes. Whilst soil pH can easily be increased by application of lime, in practice application must be economically viable with yield benefits offering an acceptable return on investments. Liming is a long-term investment with benefits becoming apparent over multiple years. Long-term economic strategies can be problematic for farmers who lack investment capital and who may have short-term decision time frames, such as most smallholder farmers in sub-Saharan Africa. In addition, application of lime causes substantial greenhouse gas (GHG) emissions (especially CO2). It is currently unclear how liming affects GHG emissions per tonne of maize, in cases where liming increases crop yields.